Tell me when? - "Chancellor Press" (Chancellor Press London, 2010)
REFERENCE WORKS. Tell Me When provides fascinating answers to interesting questions which can provide teasing quiz questions, settle arguments and assist with school projects. It is an intriguing reference book for the whole family. Tell Me When: *When do igloos melt? *When is the shortest day? *When do we lose our sense of taste? *When was the television invented? Six fact-packed subject categories boost the general knowledge of your children and even you, helping to engage the whole family. Ages 7+